The distributional effects of conventional monetary policy and quantitative easing: Evidence from an estimated DSGE model - Stefan Hohberger; Romanos Priftis; Lukas Vogel (Bank of Canada, 2019)
This paper compares the distributional effects of conventional monetary policy and quantitative easing (QE) within an estimated open-economy DSGE model of the euro area. The model includes two groups of households: (i) wealthier households, who own financial assets and can smooth consumption over time, and (ii) poorer households, who only receive labor and transfer income and live "hand to mouth." We compare the impact of policy shocks on constructed measures of income and wealth inequality (net disposable income, net asset position, and relative per-capita income). Except for the short term, expansionary conventional policy and QE shocks tend to mitigate income and wealth inequality between the two population groups.
Keywords: E44; E52; E53; F41; 330; Economic models; Interest rates; Monetary policy; Transmission of monetary policy